EVALUATING THE IMPACT OF THE CONSTRUCTION SECTOR ON OTHER SECTORS USING THE COST-BENEFIT METHOD (LITERATURE REVIEW) - Jafarova, Rumella; Pervin, Quliyeva (Granthaalayah Publications and Printers, 2025)
If we consider the Cobb-Douglas production function at both the micro and macro levels, we will see that the added value generated depends on capital and labor, as well as technology. Since the product generated in the construction sector itself often plays the role of capital for other sectors, the mechanism of the impact of this sector on economic development is related to the formation of capital and the creation of new jobs. In the previous paragraphs, we focused on the added value or product volume generated in the construction sector itself and the impact of these products on GDP growth, as well as on the level of welfare. However, it should be borne in mind that the added value generated by the construction sector, regardless of its form, is intended for the long term and is aimed at economic development and improving welfare in the long term. For example, housing construction has been of great importance in improving people's welfare for decades. Irrigation systems aimed at the development of the agricultural sector play the main capital role in increasing productivity in this sector for the long term.